Feeding broilers with dry whey powder and whey protein concentrate affected productive performance, ileal digestibility of nutrients and cecal microbiota community. (7th September 2017) - Pineda-Quiroga, C.; Camarinha-Silva, A.; Borda-Molina, D.; Atxaerandio, R.; Ruiz, R.; García-Rodríguez, A.
Abstract : Dietary interventions are a common practice in the poultry industry to promote optimal performance and health of animals. Here, we aim at assessing the influence of supplementing broiler diets with dry whey powder (DWP) and whey protein concentrate (WPC) on nutrient coefficient of apparent ileal digestibility (CAID) and productive performance. Cecal microbiota composition was also determined using Illumina amplicon sequencing. Dietary treatments were control diet (no supplementation of DWP or WPC), 60-DWP (60 g/kg of DWP), and 80-WPC (80 g/kg of WPC). One-day-old male broilers were randomly assigned to one of three treatments, and housed in floor pens. In Trial 1, 90 1-day-old chicks were allocated to three pens/treatment, with 10 birds/pen, during 21 days for CAID evaluation. Diet 60-DWP increased Ca CAID ( P =0.041), while diet 80-WPC improved Ca and P CAID ( P <0.001 and 0.002, respectively) when compared with control diet. In Trial 2, 810 one-day-old chicks were allocated to nine pens/treatment, with 30 birds/pen, during 42 days. Feeding chickens with 60-DWP and 80-WPC increased their BW, average daily gain (ADG) and feed intake (FI) during the starter ( P <0.001 for all variables) and grower-finisher periods ( P <0.001 for BW and FI, and P =0.048 for ADG), and during the entire feeding period ( P <0.05), when compared with control diet. Diets 60-DWP and 80-WPC reduced the feed conversion ratio of chickens during the starter period ( P <0.001 and 0.003, respectively), while 60-DWP reduced this parameter during the entire feeding period ( P =0.048), when compared to control diet. At day 42, cecal microbial communities of chickens that were fed with 60-DWP and 80-WPC differed from those fed with control diet ( R =0.776, P =0.008; and R =0.740, P =0.008, respectively). The abundance of Bacteroides fragilis, Bacteroides spp., Escherichia coli/Shigella flexneri and Megamonas furniformis increased when 60-DWP and 80-WPC diets were offered, while the presence of Helicobacter pullorum decreased. Lactobacillus salivarius consistently increased in chickens with better feed conversion ratio, which were those fed with 60-DWP. The results obtained in the present study indicate that growth of chickens is improved by DWP and WPC supplementation because of a higher mineral digestibility, increased feed intake and modulation of cecal microbiota communities.